Observation-based temperature and freshwater noise over the Atlantic Ocean - A. A. Boot; H. A. Dijkstra; H. A. Dijkstra (Earth System Dynamics)
The ocean is forced at the surface by a heat flux and freshwater flux field from the atmosphere. Short-timescale variability in these fluxes, i.e., noise, can influence long-term ocean variability and might even affect the Atlantic meridional overturning circulation (AMOC). Often this noise is assumed to be Gaussian, but detailed analyses of its statistics appear to be lacking. Here we study the noise characteristics in reanalysis data for two fields that are commonly used to force ocean-only models: evaporation minus precipitation and 2 m air temperature. We construct several noise models for both fields, and a pointwise normal inverse Gaussian distribution model gives the best performance. An analysis of CMIP6 models shows that these models do a reasonable job at representing the standard deviation and skewness of the noise, but the excess kurtosis is more difficult to capture. The pointwise noise model performs better than the CMIP6 models and can be used as forcing in ocean-only models to study, for example, noise-induced transitions of the AMOC.